Fabrication of ascorbyl palmitate loaded poly(caprolactone)/silver nanoparticle embedded poly(vinyl alcohol) hybrid nanofibre mats as active wound dressings via dual-spinneret electrospinning. Issue 50 (20th June 2017) - Du, L.; Xu, H. Z.; Li, T.; Zhang, Y.; Zou, F. Y.
Abstract : AP loaded PCL/AgNP embedded PVA hybrid nanofibre mats were prepared through dual-spinneret electrospinning, which altogether contributed to wound healing. Abstract : In this study, a good combination consisting of poly(vinyl alcohol) (PVA) incorporated with monodisperse silver nanoparticles (AgNPs) and poly(caprolactone) (PCL) loaded with ascorbyl palmitate (AP) was introduced for wound healing. The hybrid nanofibrous mats were analysed by ultraviolet-visible spectroscopy (UV-Vis), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared spectroscopy (FTIR). UV-vis and TEM revealed the presence and morphology of well-dispersed AgNPs obtained by an in situ reduction approach in the PVA nanofibres after electrospinning. XPS and XRD results demonstrated that the AgNPs and AP were physically mixed into the PVA and PCL, respectively. Successful preparation of bicomponent polymer matrices (PVA and PCL) in the hybrid mat was confirmed by FTIR and XRD. To evaluate the cytocompatibility of the hybrid nanofibre mats, NIH-3T3 fibroblast cells were seeded on the matrix. Results showed that the incorporation of AP could weaken the toxic effects of AgNPs on cell proliferation. The antibacterial effects on Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ), and the animal wound healing capabilities were also investigated. The hybrid nanofibres mats showed a high antibacterial activity against E. coli and S. aureus . The wound healing test and histological evaluation also revealed that the AP loaded PCL/AgNP embedded PVA hybrid nanofibre mats will have potential as a wound dressing for future therapeutic biomedical applications.